Conclusion and Future Work - Dirik, Mahmut; Castillo, Oscar; Kocamaz, Fatih (Springer Science and Business Media Deutschland GmbH, 2021)
In this book, we proposed a vision-based kinematic control structure for a wheeled mobile robot (WMR) path planning and path tracking problems in a partially cluttered indoor environment using various heuristics and Soft computing algorithms. The aim was to develop a behavioral strategy for mobile robot navigation in static indoor environments. © 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.